Bridgeless Boost Pfc Converter Using The Three-state Switching Cell - Seixas, Falcondes José Mendes de; Balestero, Juan Paulo Robles; Seixas, Claudiner Mendes de; Tofoli, Fernando Lessa; Bascopé, Grover Victor Torrico (Eletrônica de Potência, 2012)
This paper introduces a bridgeless boost converter based on the three-state switching cell for PFC (power factor correction) applications, whose distinct advantages are reduced conduction losses with the use of magnetic elements with minimized size, weight, and volume. The approach also employs the principle of interleaved converters, as it can be extended to a generic number of legs per winding of the autotransformers and high power levels. The theoretical analysis of the proposed converter is developed, while a comparison with the conventional boost converter is also performed. An experimental prototype rated at 1 kW is implemented to validate the proposal, as relevant issues regarding the novel converter are discussed.